The Effect of Osteoporosis Prevention Education on Knowledge, Attitude and Behavior of Adolescent Female Students in Kermanshah, Iran - Samira Mohammadi; Fazlollah Ghofranipour; Mohammad Gholami-Fesharaki (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Osteoporosis is a common metabolic bone disorder among females. Primary prevention is the easiest and cheapest way to deal with this condition. Therefore, it is important to educate about osteoporosis risk factors and preventive behaviors during adolescence. This study aimed to evaluate the effect of osteoporosis prevention education on knowledge, attitude and practice of adolescent female students in Kermanshah, Iran. Materials and Methods: We performed this quasi-experimental research in 118 adolescent female students in Kermanshah in 2014. The participants were selected with multistage cluster sampling form guidance schools of the city. They were allocated randomly to intervention (n=53) and control (n=65) groups. We collected data by a four-part questionnaire including demographic information, knowledge, attitude and behavior about osteoporosis prevention. Data were analyzed in SPSS 19 using independent t-test, paired t-test, chi-squared and Pearson's correlation. Results: The mean scores of knowledge, attitude and practice displayed no significant difference between case and control groups at pre-intervention (P>0.05). However, the averages of knowledge (P=0.024) and attitude (P=0.003) increased significantly in the training group after performing the educational program. Although, the behavior mean had no significant difference between the two groups at post-intervention (P= 0.086). Conclusions: Educating about osteoporosis prevention led to promote the knowledge and attitude of adolescent female students in Kermanshah. However, this training had no influence on behavior. It is necessary to consider this problem in designing educational interventions in this target group.